2019
DOI: 10.17645/si.v7i4.2334
|View full text |Cite
|
Sign up to set email alerts
|

Between ‘Labour Migration’ and ‘New European Mobilities’: Motivations for Migration of Southern and Eastern Europeans in the EU

Abstract: This article investigates in comparative perspective different accounts of the motivations for migration offered by Bulgarian, Romanian, Italian and Spanish nationals living in another EU country, or planning to move. In-depth interviews yield a range of accounts for the decision to leave the home-country, from narrowly defined economic motivations, professional and ‘qualitative’ labour market considerations, to desires for cultural/lifestyle exploration. Both individual and country-level factors are mobilised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Both Figure 6 and Figure 2 indicate that the main reasons for emigration are related to wages and income (total sample average, 4.51). These results resonate with findings in other studies on migration intentions from new EU states [4,8,37,39]. Furthermore, studies looking into similar issues comment that family reasons (identified in our research with a total sample average of 2.72) rank low for young adults [26].…”
Section: The Migration Intentions Of Students In Romanian Technical Universitiessupporting
confidence: 92%
See 2 more Smart Citations
“…Both Figure 6 and Figure 2 indicate that the main reasons for emigration are related to wages and income (total sample average, 4.51). These results resonate with findings in other studies on migration intentions from new EU states [4,8,37,39]. Furthermore, studies looking into similar issues comment that family reasons (identified in our research with a total sample average of 2.72) rank low for young adults [26].…”
Section: The Migration Intentions Of Students In Romanian Technical Universitiessupporting
confidence: 92%
“…The questionnaire constructed for this research investigated engineering students' perceptions of the migration phenomenon among peers, as well as their self-assessment of the topic with respect to motivations, destinations, and personal factors influencing the decision concerning their post-graduation strategies. Consistent with other studies on migration drivers, we included in the questionnaire factors pertaining to personal motivations (individual perceptions, desires), relational motivations (family ties), and contextual conditions (technological, educational, health, political systems) [37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the uncertain future of European integration, it is important to highlight the link between early experiences of international mobility and the formation of supra-national identifications. Our Southern European interviewees frequently had enriching academic experiences abroad as young adults prior to the observed migration moment in the interviews, and that made them appreciative of their European identity-a trend that was less visible among the Eastern European interviewees (see Coletto & Fullin, 2019;Fischer-Souan, 2019;Quassoli & Dimitriadis, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As it is the case for other types of labels, such as those that concern gender or ethnicity, they are used to implicitly generate a distinction between those who have the power to impose such labels and those who have to deal with them (Gallissot, Rivera, & Kilani, 1997). Several contributions in this thematic issue, in particular Quassoli and Dimitriadis (2019) comment on the malleability of labels and on the political aspects of mobility noted in other studies as well (Conradson & Latham, 2005;Parutis, 2011). Fischer-Souan (2019, comparing mobility trajectories of Southern European and Eastern European interviewees, discussed an often drawn distinction between economic and lifestyle migrants.…”
Section: The Cultural Dimension Of Intra-eu Mobility: Identity and Belonging Beyond National Bordersmentioning
confidence: 99%